PENGARUH IPM TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI NUSA TENGGARA TIMUR - Tlali, Sisilia; Tameno, Nikson; Tiwu, Maria Indriyani Hewe (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2024)
The aim of this research is to determine the influence of the health index, education index and purchasing power index on economic growth in East Nusa Tenggara Province. The type of research is a quantitative descriptive approach while the analytical method used is statistical methods and multiple linear analysis techniques using Eviews 9. The results of this research show that the health index, education index and purchasing power index have a simultaneous effect with a significance level of 0.000. Meanwhile, partial test results showed that the health index and purchasing power index had a positive and significant effect on economic growth, while the education index had a negative and significant effect on economic growth in East Nusa Tenggara Province. The implication of this research is that with the results achieved, namely that the health index and purchasing power index play an important role in economic growth, the performance of education should be further improved by the government of East Nusa Tenggara Province. Relevant agencies should further improve their performance to improve the quality of education in East Nusa Tenggara Province. keyword : education index, health index, purchasing power index and economic growth